The Effect of Net Profit on Cash Dividends and Stock Prices as Intervening Variables in Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange 2018-2022 - Kurratul Aini; Achmad Fadjar (Journal of Economic, Bussines and Accounting (COSTING), 2024)
A positive increase in net profit can cause the stock price to rise, because this increase in stock price can affect investor perception and managerial decisions, including certainty regarding future dividend distribution. This study aims to assess the influence of net profit and cash dividends on stock prices as intevening variables. In this study, the data used is panel data, which is a combination of time series data and cross section data. The time series data used is 2018-2022. The population in this study is all mining sub-sector companies listed on the Indonesia stock exchange. The determination of the sample in this study was carried out using the purposive sampling method, with the main criterion of LQ45 index companies. The results of this study found that Net Profit has an effect on Cash Dividends, then Cash Dividends have an effect on Stock Prices.